2012
DOI: 10.1016/j.abb.2012.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic studies of the role of a conserved histidine in a mammalian polyamine oxidase

Abstract: Polyamine oxidases are peroxisomal flavoproteins that catalyze the oxidation of an endo carbon nitrogen bond of N1-acetylspermine in the catabolism of polyamines. While no structure has been reported for a mammalian polyamine oxidase, sequence alignments of polyamine oxidizing flavoproteins identify a conserved histidine residue. Based on the structure of a yeast polyamine oxidase, S. cerevisiae Fms1, this residue has been proposed to hydrogen bond to the reactive nitrogen in the polyamine substrate. The corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Lys 315 has been implicated in the oxidative half-reaction, 21 and similar roles have been proposed for the corresponding residues in SMO (Lys 367) 22 and ZmPAO (Lys 300). 23 The site of catalysis is located in the junction between the two subpockets where the catalytically important His 64 24 and the highly conserved Tyr 430 5 line a narrow groove. While the electrostatic character of the hydrophobic subpocket is neutral, the other subpocket holds two distinguishable patches of negative charge.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lys 315 has been implicated in the oxidative half-reaction, 21 and similar roles have been proposed for the corresponding residues in SMO (Lys 367) 22 and ZmPAO (Lys 300). 23 The site of catalysis is located in the junction between the two subpockets where the catalytically important His 64 24 and the highly conserved Tyr 430 5 line a narrow groove. While the electrostatic character of the hydrophobic subpocket is neutral, the other subpocket holds two distinguishable patches of negative charge.…”
Section: ■ Resultsmentioning
confidence: 99%
“…A histidine within the binding site, which is highly conserved across many polyamine oxidases, has been suggested to play a role in both directing the substrate to the catalytic site (His 64 in APAO) 24 and participating in a hydrogen bond network that is important for maintaining the overall active site structure (His 67−Asn 195−Asp 94 in Fms1). 33 Analysis of the APAO− substrate complex shows that His 64 is indeed positioned close enough to interact with N5 of N 1 -acetylspermine through a hydrogen bond at physiological pH.…”
Section: ■ Discussionmentioning
confidence: 99%
“…This review will focus on oxidases present in mammalian tissues. (There are several useful reviews on the plant and yeast polyamine oxidases and the molecular evolution of the family of polyamine oxidases. , ) Unfortunately, the nomenclature of these enzymes is confusing The mechanistic aspects of amine oxidation are well understood, and they are best characterized in terms of their cofactors and preferred substrates. Detailed mechanistic and structural studies have shown that these oxidases can be classified as Cu 2+ -containing and FAD-requiring.…”
Section: Oxidases Attacking Polyaminementioning
confidence: 99%
“…1). Among them, His82 has an important role in substrate binding (Tavladoraki et al, 2011;Adachi et al, 2012;Tormos et al, 2012) and is conserved in most PAOs involved in polyamine back-conversion, such as, for example, MmAPAO, yeast FMS1, AtPAO2, AtPAO3, and AtPAO4, but not in AtPAO1 (Fig. 1).…”
Section: Atpao5 Has Higher Sequence Similarity To Animal Paos Than Tomentioning
confidence: 99%